Skladenjska določitev lastnega imena - Šivic-Dular, Alenka (Jezik in slovstvo, 1999)
The article analyzes scholary views of the syntactic function of the two components, ?$N_1? and ?$N_2?, in noun phrases consisting of two nouns in the nomiunative case (type ?$N_1?-?$N_2?) in grammars of Slavic languages and a syntactic definition of the process of onymization is given.
Keywords: Slovene; slovenščina; onomastics; onomastika; lastna imena; skladnja; syntax